Lethal Yellowing (LY) of Palm - Nigel A. Harrison; Monica L. Elliott (EDIS)
Lethal yellowing (LY) is a palm disease prevalent in Florida landscapes in the southern one-third of the state. It is also observed in field nurseries. This disease has significantly reduced the number of tall-type Cocos nucifera (coconut) in Florida and the Caribbean Basin, and localized outbreaks continue to occur. This document is PP-222, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.